A diagnostic importance of socio-historical-cultural and educational in the indigenous communities of Peru: "in search of a new paradigm for the development of the country" - Bocangel-Weydert, Guillermo A. (2019)
An alternative of crucial importance for the development of the country at present is the search for a new paradigm model for our indigenous communities, where it is necessary to know the main conditions for achieving development in its present condition, with the completion of a socio-historical-cultural and educational diagnosis. With information about the behavior of the aforementioned variables, and using data collected from various sources, it will be achieved pose a new paradigm model, applying this model in a pilot of two indigenous communities in the department of Huánuco test. The proposed model has to allow, in the near future, provide solutions to current problems in our country.